Post-Brexit: Do board interlocks make banks take similar relocation decisions? - Robert Panitz; Johannes Glückler (ZFW - Advances in Economic Geography, 2023)
Because Brexit has implied a surge of relocation decisions by financial service firms during a short period of time, we examine the locational decisions of the financial industry in Europe. Adopting a relational perspective we analyze the association between similar relocation decisions of UK-based banks and the connectivity of their decision boards. Based on an analysis of relocation announcements in the media, press releases, and annual reports, as well as of interlocking directorships within the financial sector, our study connects research streams on relocation and internationalization with cross-board memberships and interlocks. Our findings suggest that the higher the competition between two banks and the stronger the connectivity in interlocking board memberships between them, the more likely are these banks to announce different relocation decisions. We interpret these robust findings as a behavior that effectively reduces competition for limited localized resources.
Keywords: 330; Brexit; financial industry; interlocking directorates; network analysis; relocations